2022
DOI: 10.18502/ijph.v51i6.9698
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Epidemiological Study of Human Hydatidosis in Semnan and Sorkheh, Semnan Province, Iran

Abstract: Background: To determine the seroprevalence of human cystic echinococcosis/hydatidosis which is one of the most important zoonotic diseases by ELISA using native antigen B in Semnan and Sorkheh, Semnan province, Iran, where no significant information about human infection exists. Methods: Overall, 957 human serum samples were randomly prepared from Semnan, Sorkheh, and its 13 surrounding villages in different seasons from 2017 to 2018. Antigen B was prepared from native hydatid cyst fluid of domestic she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a study, on all outbreaks caused by food in Semnan Province, it has shown that the prevalence rate was higher in women than in children and men (46%). The frequency of outbreaks in 24-44 years was observed more than in other groups (31.57%) [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a study, on all outbreaks caused by food in Semnan Province, it has shown that the prevalence rate was higher in women than in children and men (46%). The frequency of outbreaks in 24-44 years was observed more than in other groups (31.57%) [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 76%
“…Foodborne diseases are one of the most important problems, especially in developing countries, and they are one of the main factors in morbidity and mortality all over the world. Food is an important carrier in the transmission of microorganisms to humans, and among these microorganisms, Salmonella is still the main cause of foodborne diseases in the pathogenesis of humans throughout the world [13][14][15]31].…”
Section: Discussionmentioning
confidence: 99%
“…Different antigens including native, semi purified or recombinant have been used for CE diagnosis ( 16 , 19 , 25 29 ). They have been used for both diagnostic and sero-epidemiological purposes ( 26 , 30 – 34 ). Although, lyophilized antigens have been used in limited studies ( 21 , 22 ), but the validity of lyophilized HCF and AgB has not been evaluated and compared.…”
Section: Discussionmentioning
confidence: 99%